2018
DOI: 10.1063/1.5027596
|View full text |Cite
|
Sign up to set email alerts
|

Carrier relaxation bottleneck in type-II InAs/InGaAlAs/InP(001) coupled quantum dots-quantum well structure emitting at 1.55 μm

Abstract: Carrier relaxation in self-assembled InAs/In0.53Ga0.23Al0.24As/InP(001) quantum dots emitting at 1.55 μm and quantum dots coupled to the In0.64Ga0.36As/In0.53Ga0.23Al0.24As quantum well through a thin In0.53Ga0.23Al0.24As barrier is investigated employing high-temporal-resolution (< 0.3 ps), time-resolved spectroscopic techniques at cryogenic temperatures, supported additionally with photoluminescence, photoluminescence excitation, and theoretical modelling. We focused on intra-band carrier relaxation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Th tained PL decay time approximates well the radiative lifetime, which cor maximal single-photon emission rate of 0.5 GHz. However, this is just which is usually not achieved in the final SPS device due to the finite extr of the emission, nonideal internal quantum efficiency of the emitters, as w The photoluminescence lifetime and its accuracy determined from the fit with a monoexponential decay (red dotted line in Figure 3) is (1.78 ± 0.02) ns, which is similar to the values reported for other InAs on InP QD-like structures [20,51,60,63,[68][69][70]. The measurement was performed at low excitation power (0.1 µW) to minimize the probability of occupation of higher energy states, which would affect the PL lifetime.…”
Section: Resultssupporting
confidence: 77%
“…Th tained PL decay time approximates well the radiative lifetime, which cor maximal single-photon emission rate of 0.5 GHz. However, this is just which is usually not achieved in the final SPS device due to the finite extr of the emission, nonideal internal quantum efficiency of the emitters, as w The photoluminescence lifetime and its accuracy determined from the fit with a monoexponential decay (red dotted line in Figure 3) is (1.78 ± 0.02) ns, which is similar to the values reported for other InAs on InP QD-like structures [20,51,60,63,[68][69][70]. The measurement was performed at low excitation power (0.1 µW) to minimize the probability of occupation of higher energy states, which would affect the PL lifetime.…”
Section: Resultssupporting
confidence: 77%
“…However, the uncertainty of experimental values does not allow this result to be verified. At the emission energy of 0.84 eV, a similar PL lifetime of ∼ 1.65 ns has been obtained for slightly in-plane asymmetric S-K InAs/InAlGaAs/InP(001) QDs [31]. For highly asymmetric confining potentials like those in InAs/InAlGaAs/InP(001) quantum dashes, the PL lifetime consists of two short and long components [30].…”
Section: Carrier Dynamicssupporting
confidence: 61%
“…1 and shows two noticeable Δ𝑅/𝑅 features settled in the ranges of 1.13-1.20 eV and 0.92-0.96 eV, respectively. While the former is attributed to optical absorption involving valence and conduction bands of the InAlGaAs barrier [31], the latter is tentatively assigned to absorption in the WL. The WL-related feature appears to be constituted by at least two transitions centered at ∼0.93 eV and ∼0.94 eV.…”
Section: A Modulated Reflectivity and Photoluminescencementioning
confidence: 99%
“…For a self-assembled InAs/GaAs QD the intra-band relaxation time reaches several ps [39]. In a very recent study on intra-band carrier relaxation times in selfassembled InAs/InP QDs it was shown that relaxation times can be as short as 8 ps at cryogenic temperatures, even including the capture time [40]. For a comparable QD system like InAs/InAlAs/InP(001) [41] and InAs/InP(311B) [42], or InAs/InGaAsP/InP(001) quantum dashes [43], the intra-band relaxation time is reported within the range of 1-40 ps.…”
Section: Optical Characterizationmentioning
confidence: 99%